[At Paso Robles High School] - Cayetano Contreras, Jr.::::::photographer::: (2005)
Description supplied by photographer: 'Esto es en la escuela secundaria de Paso Robles. La foto es de mi tío Tony hablando con su novia. El le estaba pidíendo perdón mientras le regalaba una flor y le decía que sin ella el no puede vivir.' - 'At Paso Robles High School. I took this photo of my uncle Tony telling his girlfriend to forgive him for messing up on her. He is giving her a flower and telling her that without her he is nothing.'